Process for recycling and preparing lithium-containing precursor of positive electrode material and positive electrode material

Through the reduction treatment, acid leaching and spray pyrolysis processes of waste lithium battery positive electrode materials, the high energy consumption and environmental pollution problems in the recycling technology of lithium battery positive electrode materials are solved, and efficient recycling of lithium, nickel, cobalt and manganese are achieved and positive electrodes are achieved. The low-cost production of material precursors improves product performance and production efficiency.

CN119265426APending Publication Date: 2025-01-07HUNAN LEAGUER HOPE TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310820750.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-05
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing lithium battery positive electrode material recycling technology has high energy consumption, low recovery rate and environmental pollution problems, and the traditional synthesis process is complex and costly, so it is impossible to effectively recover precious metals such as lithium, nickel, cobalt, and manganese.

Method used

By reducing the positive electrode material of the used lithium battery, a solid-liquid mixture of metal salt is obtained by acid leaching method, and after filtration and decomposition treatment, a lithium-containing precursor is prepared by spray pyrolysis method to reduce the process and improve the production efficiency and avoid wastewater produce.

Benefits of technology

It realizes efficient recycling of precious metals such as lithium, nickel, cobalt, manganese and the production of positive electrode material precursors, which reduces production costs, reduces environmental pollution, and improves the low impurity content and performance of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119265426A_ABST
    Figure CN119265426A_ABST
Patent Text Reader

Abstract

The invention provides a process for recovering and preparing a lithium-containing precursor of a positive electrode material and the positive electrode material from a waste lithium battery positive electrode material. The invention also provides the lithium-containing precursor of the positive electrode material and the positive electrode material. According to the process, lithium, nickel, cobalt, manganese and other noble metals are recycled, and the positive electrode material precursor and the positive electrode material are further prepared through a spray pyrolysis method, so that the environmental pollution problem of the waste lithium battery positive electrode material is relieved, the pressure of noble metal resource exploitation is relieved, and the cost of preparing the positive electrode material precursor and the positive electrode material is also reduced; and less waste materials such as waste water are discharged in the process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of positive electrode materials for lithium batteries, and in particular to a process for preparing positive electrode material lithium-containing precursors and positive electrode materials by recycling waste positive electrode materials for lithium batteries. Background Art

[0002] Lithium-ion batteries have been widely used in portable electronic devices and new energy vehicles due to their high energy density, good cycle stability, low memory effect and environmental friendliness. China's large-scale mass production of new energy vehicles began in 2014, and the life of power batteries is generally 5-8 years. As the earliest batch of large-scale power batteries have reached the retirement age since 2019, China retired about 30,000 tons of power batteries in 2020. The positive electrode materials of power batteries contain heavy metals such as cobalt, nickel, and manganese. If the positive electrode materials of these retired power batteries are not treated, they will seriously pollute the environment.

[0003] On the other hand, China is highly dependent on foreign lithium resources, and it is difficult to mine local mineral resources. China is short of cobalt resources, and the reserves of cobalt concentrate are extremely small. However, cathode materials contain a large amount of precious metals such as lithium, nickel, cobalt, and manganese. Therefore, recycling lithium, nickel, cobalt, manganese and other precious metals from cathode materials will ease the pressure of resource mining.

[0004] Recycling companies usually focus on the high-value transformation of cobalt and nickel, while weakening the recycling value of lithium. Lithium is usually precipitated as a by-product or enriched in slag, failing to achieve efficient recycling. For example, the Umicore process, lithium-ion batteries are initially disassembled to remove metal or plastic shells and then put into a vertical furnace, and high-temperature reduction smelting is used to obtain metal alloys such as nickel, cobalt, and copper. Metals such as lithium and aluminum are enriched in the smelting slag. This process has high energy consumption, low metal recovery rate, high equipment requirements, and cannot recover lithium. Metal recovery in alloys requires further refining, etc.; environmental impacts include the output of smelting slag, dust, and harmful waste gas.

[0005] In addition, power batteries account for a high proportion of the cost of new energy vehicles, and positive electrode materials account for more than 50% of the cost of battery cells. At present, the commonly used positive electrode material synthesis technology route in the world is: nickel, cobalt and manganese soluble salts are accurately proportioned and dissolved, and then precipitated and crystallized into nickel, cobalt and manganese hydroxide. After filtering, washing, drying and other processes, nickel, cobalt and manganese hydroxide is calcined to obtain nickel, cobalt and manganese oxide, which is mixed with lithium salt ball milling, pre-baked, sintered and then crushed into nickel cobalt manganese oxide products. The preparation process has more than a dozen steps. There are: 1) The chemical precipitation and crystallization process will produce a large amount of ammonia-containing wastewater. Although environmental protection measures such as ammonia evaporation and oxidation to remove ammonia are taken, there are still major environmental risks; 2) The process is long, the process is complicated, and the production cost is high. If the positive electrode material can be recycled from waste positive electrode materials, one or more defects of the above precipitation method may be solved.

[0006] Therefore, there is a need to develop a method for efficiently recovering precious metals such as lithium, nickel, cobalt, and manganese from waste lithium battery positive electrode materials. Summary of the invention

[0007] The inventors have developed a production process through intensive research and development for recovering precious metals such as lithium, nickel, cobalt, and manganese from waste lithium battery positive electrode materials, and further preparing positive electrode material precursors and positive electrode materials through spray pyrolysis. This reduces the environmental pollution problem of waste lithium battery positive electrode materials, eases the pressure of precious metal resource mining, and reduces the cost of preparing positive electrode material precursors and positive electrode materials. In addition, less wastewater and other waste materials are discharged in the process.

[0008] The first aspect of the present application provides a method for preparing a lithium-containing precursor of a positive electrode material, comprising:

[0009] Step 1) reducing the waste lithium battery positive electrode material to obtain lithium-containing powder;

[0010] Step 2) treating the lithium-containing powder with at least one acid selected from oxalic acid, acetic acid, formic acid, nitric acid, sulfuric acid, and hydrochloric acid to obtain a corresponding metal salt solid-liquid mixture;

[0011] Step 3) filtering the metal salt solid-liquid mixture to obtain a filtrate;

[0012] Step 4) removing impurities from the filtrate to obtain a cleansed liquid;

[0013] Step 5) spray pyrolysis the impurity removal liquid to obtain a lithium-containing precursor of the positive electrode material.

[0014] This application uses waste battery positive electrode materials as the main raw materials to prepare lithium-containing precursors and positive electrode materials, which can realize resource recycling and reduce production costs; at the same time, the process of this application not only recovers precious metals such as nickel, cobalt, and manganese, but also effectively recovers lithium, and the lithium, nickel, cobalt, and manganese metal salt solutions obtained by recycling can be conveniently and efficiently used to synthesize positive electrode material precursors, reducing the process of separating metals such as lithium, nickel, cobalt, and manganese, further reducing costs. Since lithium, nickel, cobalt, and manganese metal salts have relatively high impurities, the impurity content in the impurity removal liquid of the product before spray pyrolysis is at a low level through the impurity removal treatment of this application, ensuring the low impurity content in the lithium-containing precursor product. Since this application forms a lithium-containing precursor by spray pyrolysis, compared with the coprecipitation method, the process of this application does not produce wastewater.

[0015] The lithium-containing precursor of the positive electrode material in this application is formed by atomization roasting. Compared with the hydroxide precursor prepared by the coprecipitation method, the process of this application is simple, with fewer intermediate processes, and the reaction process is easy to flexibly control. The roasting treatment is carried out while atomizing, which not only ensures that the product has a smaller particle size, but also has a fast reaction speed. The actual reaction time for obtaining the lithium-containing precursor of the positive electrode material by atomization roasting is only a few seconds, and the production efficiency is high. In addition, since the anions in the salt solution are converted into gaseous substances in a high-temperature environment and removed or recycled, the raw material utilization rate is high, the impurity content in the product is low, and the performance is excellent.

[0016] The second aspect of the present application provides a positive electrode material precursor prepared by the method of the first aspect of the present disclosure.

[0017] The lithium-containing precursor disclosed in the present application is an oxide lithium-containing precursor. When the lithium-containing precursor is sintered into a positive electrode material, no waste water is generated due to the absence of hydroxide. The lithium-containing precursor exists in the form of an oxide. Compared with a traditional hydroxide precursor, the content of the main metals of nickel, cobalt and manganese in the oxide precursor is higher. At the same time, the precursor also contains lithium. When sintered into a positive electrode material, the decomposition of lithium salt carbonate during the sintering of the positive electrode material is reduced, and the yield of the finished product under the same loading amount is improved, thereby increasing the output when sintering into the positive electrode material, reducing the manufacturing cost of the positive electrode material, and greatly increasing the production line capacity.

[0018] The lithium-containing precursor in this application is formed by atomization roasting. Compared with the hydroxide precursor prepared by the coprecipitation method, the process of this application is simple, with few intermediate processes, and the reaction process is easy to flexibly control. The roasting process is carried out while atomizing, which not only ensures that the product has a smaller particle size, but also the product has a fast reaction speed. The actual reaction time of obtaining the lithium-containing precursor material by atomization roasting is only a few seconds, and the production efficiency is high. In addition, since the anions in the salt solution are converted into gaseous substances in a high temperature environment to be removed or recycled, the raw material utilization rate is high, the impurity content in the product is low, and the performance is excellent. At the same time, the lithium-containing precursor material product prepared by this method has a more excellent structural stability of the material itself relative to the traditional coprecipitation method.

[0019] The third aspect of the present application provides a method for preparing a positive electrode material, which comprises calcining the lithium-containing precursor of the positive electrode material of the second aspect of the present disclosure to obtain a lithium-containing positive electrode material.

[0020] The fourth aspect of the present application provides a positive electrode material prepared by the method of the third aspect of the present disclosure. The electrochemical performance of the positive electrode material provided by the fourth aspect of the present application is acceptable and comparable to that of the positive electrode material prepared by the traditional precipitation method. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings of the embodiments will be briefly introduced below. Obviously, the drawings in the following description only relate to some embodiments of the present invention, but are not intended to limit the present invention.

[0022] Figure 1 The present invention discloses a flow chart of preparing a lithium-containing precursor for a positive electrode material according to an embodiment of the present invention.

[0023] Figure 2 A flow chart for preparing a positive electrode material according to an embodiment of the present disclosure.

[0024] Figure 3 This is a SEM photograph of a lithium-containing precursor of a positive electrode material prepared according to an embodiment of the present disclosure. DETAILED DESCRIPTION

[0025] The present invention may be implemented in other specific forms without departing from the basic attributes of the present invention. It should be understood that, without conflict, any and all embodiments of the present invention may be combined with the technical features in any other embodiment or multiple other embodiments to obtain other embodiments. The present invention includes other embodiments obtained by such combination.

[0026] All publications and patents mentioned in this disclosure are hereby incorporated by reference into this disclosure in their entirety. If the purposes or terms used in any publications and patents incorporated by reference conflict with the purposes or terms used in this disclosure, then the purposes and terms of this disclosure shall prevail.

[0027] The section headings used herein are for organizational purposes only and are not to be construed as limiting the subject matter described.

[0028] Unless otherwise specified, all technical and scientific terms used herein have the common meaning in the field to which the claimed subject matter belongs. If there are multiple definitions for a term, the definition herein shall prevail.

[0029] Except in the working examples or otherwise indicated, all numbers stating quantitative properties such as particle size in the specification and claims should be understood to be modified by the term "about" in all cases. It should also be understood that any numerical range recited in this application is intended to include all subranges within the range and any combination of the various endpoints of the range or subrange.

[0030] The words "include", "contain" or "comprises" and the like used in the present disclosure mean that the elements preceding the word include the elements listed after the word and their equivalents, without excluding unrecorded elements. The terms "contain" or "includes" used herein may be open, semi-closed and closed. In other words, the term also includes "consisting essentially of" or "consisting of".

[0031] The term "optionally" in this disclosure means that the described circumstances may or may not occur.

[0032] The term "positive electrode material precursor" in the present disclosure refers to a substance before the high temperature sintering step in the process of preparing positive electrode materials (hereinafter sometimes referred to as "precursor"). The term "positive electrode material lithium-containing precursor" refers to the positive electrode material precursor containing lithium.

[0033] Unless otherwise specified, the term "lithium (Li)" does not refer to a single substance of Li metal but refers to the Li element. The same applies to expressions of other elements such as Ni, Co, and Mn.

[0034] The concentration of metal ions in this application can be measured by ICP testing, for example, by using Thermo Fisher ICP-OES to test the content of Li, Ni, Co, Mn and impurity ions.

[0035] The concentration of chloride ions in this application can be tested by using a potentiometric titrator (silver nitrate standard titration solution).

[0036] The term "reduction furnace" in this application refers to a reactor used to reduce metals from a high oxidation state to a low oxidation state. There are no particular restrictions on its shape, size, and material, but the reactor is required to be resistant to high temperatures, for example, able to be heated to 800 degrees Celsius.

[0037] The term "dissolution tank" in this application refers to a reactor for reacting lithium-containing powder with acid. There is no particular restriction on its shape, size, and material, but the reactor is required to be resistant to acid corrosion.

[0038] The first aspect of the present application provides an implementation scheme, such as Figure 1 As shown, it is a method for preparing a lithium-containing precursor of a positive electrode material, comprising:

[0039] Step 1) reducing the waste lithium battery positive electrode material to obtain lithium-containing powder;

[0040] Step 2) treating the lithium-containing powder with at least one acid selected from oxalic acid, acetic acid, formic acid, nitric acid, sulfuric acid, and hydrochloric acid to obtain a corresponding metal salt solid-liquid mixture;

[0041] Step 3) filtering the metal salt solid-liquid mixture to obtain a filtrate;

[0042] Step 4) removing impurities from the filtrate to obtain a cleansed liquid; and

[0043] Step 5) spray pyrolysis the impurity removal liquid to obtain a lithium-containing precursor of the positive electrode material.

[0044] The process of the present application not only recycles precious metals such as nickel, cobalt, and manganese, but also effectively recycles lithium. The recovered lithium, nickel, cobalt, and manganese metal salt solutions can be conveniently and efficiently used to synthesize positive electrode material precursors.

[0045] Step 1) Reducing the waste lithium battery positive electrode material to obtain lithium-containing powder

[0046] The waste lithium battery positive electrode material in step 1) can be obtained from the waste lithium battery by conventional methods, for example, the waste lithium battery is fully discharged and then mechanically disassembled, and the waste lithium battery positive electrode material is obtained by mechanical separation, grinding, and screening. See "Research Progress in Recycling Technology of Lithium Ion Batteries" by Li Mian et al., Rare Metals, Vol. 46, No. 3, pp. 349-366. The waste lithium battery can be, for example, a waste lithium battery of nickel cobalt manganese (NCM), a waste lithium battery of nickel cobalt aluminum (NCA), a waste lithium battery of cobalt oxide, a waste lithium battery of manganese oxide, or a waste lithium battery of nickel oxide.

[0047] Positive electrode materials of used lithium batteries can also be purchased from dismantling plants or environmental technology companies that specialize in the dismantling of used lithium batteries.

[0048] The source of the positive electrode material of waste lithium batteries is not limited in this application.

[0049] The waste lithium battery positive electrode material in the present application can be the one from which the binder (such as polyvinylidene chloride, soluble polytetrafluoroethylene, styrene-butadiene rubber, hydroxypropyl methylcellulose, methylcellulose, carboxymethyl cellulose, polyvinyl alcohol, acrylonitrile copolymer, sodium alginate, chitosan and chitosan) and the conductive agent (such as graphite, carbon black, acetylene black) have been basically removed, or the binder and the conductive agent have not been removed.

[0050] In one embodiment, step 1) comprises:

[0051] Step 1a) placing the waste lithium battery positive electrode material in a reduction furnace;

[0052] Step 1b) introducing a reducing agent into the reduction furnace; and

[0053] Step 1c) heating the reduction furnace, and reducing the high-valent metal ions in the waste lithium battery positive electrode material to low-valent metal ions to obtain the lithium-containing powder.

[0054] For example, the cathode material of waste lithium batteries in step 1a) is a cathode material of waste lithium nickel cobalt manganese (NCM) batteries, a cathode material of waste lithium nickel cobalt aluminum (NCA) batteries, a cathode material of waste lithium cobalt oxide batteries, a cathode material of waste lithium manganese oxide batteries, or a cathode material of waste lithium nickel oxide batteries; the reducing agent in step 1b) is selected from one or more of hydrogen, methane, carbon powder, acetylene, coal gas, and liquefied petroleum gas. In consideration of cost and safety, methane is preferably used as the reducing agent. The main component of natural gas is methane (volume content greater than 85%), so natural gas can be used as methane in this application.

[0055] When the positive electrode material of the waste lithium battery is nickel cobalt manganese oxide (NCM) waste lithium battery positive electrode material, methane high-temperature reduction can obtain a mixture of elemental nickel, elemental cobalt, nickel oxide, cobalt oxide, manganese monoxide, manganese dioxide, lithium oxide, lithium carbonate, etc.

[0056] When the positive electrode material of the waste lithium battery is nickel cobalt aluminum (NCA) waste lithium battery positive electrode material, methane high-temperature reduction can obtain a mixture of lithium aluminate, lithium carbonate, nickel oxide, cobalt oxide, elemental nickel, elemental cobalt, aluminum oxide, etc.

[0057] When the positive electrode material of the waste lithium battery is lithium cobalt oxide waste lithium battery positive electrode material, methane high temperature reduction can obtain a mixture of elemental cobalt, cobalt oxide, lithium oxide, lithium carbonate, etc. When the positive electrode material of the waste lithium battery is lithium manganate waste lithium battery positive electrode material, methane high temperature reduction can obtain a mixture of manganese monoxide, manganese dioxide, lithium oxide, lithium carbonate, etc. When the positive electrode material of the waste lithium battery is lithium nickel oxide waste lithium battery positive electrode material, methane high temperature reduction can obtain a mixture of elemental nickel, nickel oxide, lithium oxide, lithium carbonate, etc.

[0058] Step 1c) heats the reduction furnace, for example, is heated to between 400-780 degrees Celsius, and the duration of the reduction treatment is 1-10 hours. Under this reduction reaction condition, not only can the high-valent metal ions in the waste lithium battery positive electrode material be reduced to low-valent states, but also the binding agent and the conductive agent (the decomposition temperatures of acetylene black and PVDF are 306 and 316 degrees Celsius, respectively) can be effectively removed. The temperature of the reduction treatment is too low or the duration is too short, and the effect of removing the binding agent and the conductive agent is not good enough on the one hand. The temperature of the reduction treatment is too high or the duration is too long, and the energy consumption is high on the one hand, and the volatilization of lithium is increased on the other hand.

[0059] In one embodiment, the waste lithium battery positive electrode material in step 1a) is nickel cobalt manganese (NCM) or nickel cobalt aluminum (NCA) waste lithium battery positive electrode material; the reducing agent in step 1b) is methane, for example, 3 cubic meters of natural gas is introduced for every 10 kilograms of waste lithium battery positive electrode material; the reduction furnace in step 1c) is heated to between 650-730 degrees Celsius, and the reduction treatment lasts for 1-5 hours.

[0060] In another embodiment, the waste lithium battery positive electrode material in step 1a) is a waste lithium cobalt oxide positive electrode material, a waste lithium manganese oxide positive electrode material or a waste lithium nickel oxide positive electrode material.

[0061] The reducing agent in step 1b) is methane; the reduction furnace in step 1c) is heated to between 600-680 degrees Celsius, and the duration of the reduction treatment is 1-5 hours.

[0062] After high-temperature reduction, the material is cooled and ground, and the obtained lithium-containing powder is used in the acid leaching step and can also be used to adjust the pH in the impurity removal step.

[0063] Reduction of high-valent metal ions in the cathode materials of waste lithium batteries to low-valent states will facilitate acid leaching of nickel, cobalt and manganese ions without the need for traditional acid leaching with the aid of hydrogen peroxide.

[0064] Step 2) treating the lithium-containing powder with at least one acid selected from oxalic acid, acetic acid, formic acid, nitric acid, sulfuric acid, and hydrochloric acid to obtain a corresponding metal salt solid-liquid mixture

[0065] The acid leaching process in the present application is different from the traditional acid leaching process, and solutions of lithium salts, nickel salts, cobalt salts and manganese salts can be obtained without adding hydrogen peroxide.

[0066] For example, step 2) includes:

[0067] placing the lithium-containing powder and the at least one acid into a dissolving tank to react to obtain a solid-liquid mixture of a metal salt; and

[0068] Recycle waste from the dissolving tank.

[0069] In view of cost, the at least one acid is preferably an inorganic acid, such as nitric acid, sulfuric acid, hydrochloric acid or a mixture thereof.

[0070] The reaction temperature of the at least one acid and the lithium-containing powder is preferably 60-80 degrees Celsius, and the reaction time is 1-5 hours. More preferably, the reaction temperature of the at least one acid and the lithium-containing powder is 65-75 degrees Celsius, and the reaction time is 2-4 hours.

[0071] For example, 8 liters of 30% nitric acid solution is added per kilogram of lithium-containing powder at a rate of 100 ml of nitric acid solution per minute, and the reaction is carried out at 60-80 degrees Celsius for about 2 hours to obtain a metal nitrate solution.

[0072] For example, 15 liters of 10% sulfuric acid solution is added to each kilogram of lithium-containing powder at a feeding rate of 150 ml of sulfuric acid solution per minute, and the reaction is carried out at 60-80 degrees Celsius for about 2 hours to obtain a metal sulfate solution.

[0073] For example, 12 liters of 18% hydrochloric acid solution is added to each kilogram of lithium-containing powder at a rate of 120 ml of hydrochloric acid solution per minute, and the reaction is carried out at 60-80 degrees Celsius for about 2 hours to obtain a metal hydrochloride solution.

[0074] When sulfuric acid is used, the reaction of lithium-containing powder with sulfuric acid will produce waste sulfur oxides such as sulfur trioxide in the recovery and dissolution tank. When nitric acid is used, the reaction of lithium-containing powder with nitric acid will produce waste nitrogen oxides such as nitrogen dioxide or nitrogen oxide in the recovery and dissolution tank. The waste generated in the recovery and dissolution tank may include: cooling the generated nitrogen oxides or sulfur oxides to less than 30 degrees Celsius, multi-stage water absorption, air or pure oxygen oxidation to obtain nitric acid / sulfuric acid, and the nitric acid / sulfuric acid can be recycled.

[0075] Step 3) filtering the metal salt solid-liquid mixture to obtain a filtrate

[0076] The solid-liquid mixture of the metal salt obtained in step 2) can be subjected to solid-liquid separation by conventional industrial filtration methods such as pressure filtration, vacuum filtration and centrifugal filtration to obtain a filtrate. In view of cost and convenience, it is preferred that pressure filtration is used for solid-liquid separation. Pressure filtration can be carried out, for example, by a plate and frame filter press, a chamber filter press, a vertical filter press or a belt filter press.

[0077] Step 4) removing impurities from the filtrate to obtain a decontaminated liquid

[0078] The impurity ions in the filtrate obtained in step 3) may include one or more impurity ions of aluminum, iron, copper, calcium, magnesium, chromium, cadmium, chlorine or fluorine. Step 4) removes these impurity ions by generating a precipitate. The precipitate is separated into solid and liquid by, for example, filter pressing to obtain a filter residue. In the following impurity removal step, the nitrate filtrate obtained by using nitric acid in the acid leaching step is used as an example. If sulfuric acid is used in the acid leaching step, the nitric acid / nitrate added in the following impurity removal is replaced by sulfuric acid / sulfate.

[0079] In one embodiment, step 4) comprises:

[0080] Step 4a) adjusting the pH of the filtrate to 2.9-5, preferably 2.9-3.5, with lithium-containing powder, and filtering to obtain an intermediate filtrate; passing oxygen or air or adding hydrogen peroxide to the intermediate filtrate at 50 to 70 degrees Celsius to adjust the redox potential to 280mv-500mv (measured by a potentiometer) to obtain a solid-liquid mixture; filtering the solid-liquid mixture, and then returning the filter residue to the filtrate to be adjusted to a pH of 2.9-5.

[0081] In this step, the lithium-containing powder from step 1) is used to adjust the pH, instead of sodium hydroxide and ammonia water, thereby avoiding the introduction of new chemicals into the filtrate.

[0082] Here, oxygen or air or hydrogen peroxide is added to adjust the redox potential in any of the following three ways: 1. oxygen or air is exposed through a perforated tube; 2. oxygen or air is passed through a venturi to achieve gas-liquid mixing; 3. hydrogen peroxide is added to the filtrate. Sodium hypochlorite is not used to adjust the redox potential here to avoid introducing new compounds into the filtrate.

[0083] The redox potential is between 280mv and 500mv, and the iron element will be oxidized to trivalent iron and precipitated in the form of ferric hydroxide. Step 4a) can not only remove the impurity iron, but also remove the impurities Cr and Cd. For example, after the impurity removal in step 4a), the concentration of Fe, Cr, and Cd ions in the filtrate is less than 1ppm.

[0084] In this step, "returning the filter residue to the filtrate whose pH is to be adjusted to 2.9-5" can stabilize the pH value of the filtrate.

[0085] In one embodiment, step 4) comprises:

[0086] Step 4b) The pH of the filtrate is adjusted to 1.5-3.0 with an acid (e.g., 500 ml of 30% nitric acid per cubic meter of filtrate), a copper nitrate solution is added in an amount of 1:1 to 5:1, preferably 1.2:1 to 2:1, to the molar ratio of copper nitrate to chloride ions in the filtrate, and then elemental copper is added in an amount of 1:1 to 5:1, preferably 1.2:1 to 2:1, to the molar ratio of copper to chloride ions in the filtrate, and the reaction is carried out at 50 to 70 degrees Celsius for 1-3 hours, and then filtered to obtain a filtrate. The nitric acid and copper nitrate added in this step 4b) can also be replaced by sulfuric acid and copper sulfate.

[0087] Step 4b) removes chloride ions from the filtrate by converting chloride ions into cuprous chloride precipitates, and this step can reduce the chloride ion concentration in the filtrate to below 20 ppm. Step 4b) is optional. If hydrochloric acid is not used as at least one acid in step 2), the chloride ion concentration in the filtrate is generally low, and step 4b) may not be performed.

[0088] In one embodiment, step 4) comprises:

[0089] Step 4c) The pH of the filtrate is adjusted to 3.5-5.5, preferably 3.5-4.5, with lithium-containing powder (for example, 1 kg of lithium-containing powder is added per cubic meter of filtrate), filtered, and then MnF2 is added to the filtrate at a ratio of MnF2 to the total molar number of calcium and magnesium ions in the filtrate of 1:1 to 4:1, reacted at 50 to 70 degrees Celsius for 3-5 hours, then filtered, and the filter residue is returned to the filtrate to be adjusted to a pH of 3.5-5.5.

[0090] Step 4c) by adding fluoride, calcium ions and magnesium ions are precipitated into calcium fluoride and magnesium fluoride, which can reduce the calcium ions in the filtrate to less than 5ppm, and the magnesium ions to less than 20ppm. Here, the fluoride is selected as MnF2, on the one hand, to avoid introducing new impurity ions into the filtrate as much as possible, and on the other hand, MnF2 has good water solubility.

[0091] Lithium fluoride is a slightly soluble substance. When removing calcium and magnesium, part of the lithium will be precipitated in the form of fluoride. Therefore, it is preferred to return the filter residue to the filtrate to be adjusted to pH 3.5-5.5 to reduce lithium loss.

[0092] In one embodiment, step 4) comprises:

[0093] Step 4d) Aluminum nitrate solution is added to the filtrate at a molar ratio of aluminum nitrate to fluoride ions in the filtrate of 1:2 to 5:1, preferably 1:2 to 1.5:1, and aluminum oxide powder is added at a molar ratio of aluminum oxide to fluoride ions in the filtrate of 1:2 to 1:1, and the reaction is carried out at 50 to 70 degrees Celsius for 3-5 hours, followed by filtering, and the filter residue is returned to the filtrate to be added with aluminum nitrate solution and aluminum oxide powder. The aluminum nitrate in this step 4d) can also be replaced with aluminum sulfate.

[0094] In step 4d), fluoride ions are removed by the precipitation of aluminum fluoride and the adsorption of aluminum oxide, and the fluoride ions in the filtrate can be reduced to less than 5 ppm. Since aluminum oxide is an adsorbent, it may also adsorb ions such as nickel, cobalt, manganese and lithium. Therefore, in step 4d), the filter residue is returned to the filtrate to be added with aluminum nitrate solution and aluminum oxide powder.

[0095] In one embodiment, step 4) comprises:

[0096] Step 4e) adding elemental nickel, manganese or cobalt powder to the filtrate in a ratio of 5:1 to 10:1 of elemental nickel, manganese or cobalt powder to the total molar number of copper ions and aluminum ions in the filtrate, reacting at 50 to 70 degrees Celsius for 5-7 hours, then filtering, and returning the filter residue to the filtrate to be added with elemental nickel, manganese or cobalt powder.

[0097] In step 4e), a large amount of elemental nickel, manganese or cobalt powder is added to the filtrate to raise the pH of the filtrate to 4.5-6.0, preferably 4.5-5.0, and the copper ions and aluminum ions are removed in the form of hydroxide precipitation.

[0098] The elemental nickel, manganese or cobalt powder added in step 4e) is greatly excessive, and the filter residue contains a large amount of elemental nickel, manganese or cobalt powder. Therefore, the filter residue is returned to the filtrate to be added with elemental nickel, manganese or cobalt powder to avoid the loss of nickel, manganese or cobalt.

[0099] In one embodiment, step 4) comprises:

[0100] Step 4a) adjusting the pH of the filtrate to 2.9-5, preferably 2.9-3.5, with lithium-containing powder, and filtering to obtain an intermediate filtrate; passing oxygen or air or adding hydrogen peroxide to the intermediate filtrate at 50 to 70 degrees Celsius to adjust the redox potential to 280mv-500mv (measured by a potentiometer) to obtain a solid-liquid mixture; filtering the solid-liquid mixture, and then returning the filter residue to the filtrate to be adjusted to a pH of 2.9-5;

[0101] Step 4c) adjusting the pH of the filtrate to 3.5-5.5, preferably 3.5-4.5, with lithium-containing powder (for example, adding 1 kg of lithium-containing powder per cubic meter of filtrate), filtering, and then adding MnF2 to the filtrate at a ratio of MnF2 to the total molar number of calcium and magnesium ions in the filtrate of 1:1 to 4:1, reacting at 50 to 70 degrees Celsius for 3-5 hours, then filtering, and returning the filter residue to the filtrate to be adjusted to a pH of 3.5-5.5;

[0102] Step 4d) adding aluminum nitrate solution to the filtrate at a molar ratio of aluminum nitrate to fluoride ions in the filtrate of 1:2 to 5:1, preferably 1:2 to 1.5:1, and adding aluminum oxide powder at a molar ratio of aluminum oxide to fluoride ions in the filtrate of 1:2 to 1:1, reacting at 50 to 70 degrees Celsius for 3-5 hours, then filtering, and returning the filter residue to the filtrate to be added with aluminum nitrate solution and aluminum oxide powder. The aluminum nitrate in this step 4d) can also be replaced with aluminum sulfate; and

[0103] Step 4e) Add elemental nickel, manganese or cobalt powder to the filtrate in an amount of 5:1 to 10:1 of elemental nickel, manganese or cobalt powder to the total molar number of copper ions and aluminum ions in the filtrate, react at 50 to 70 degrees Celsius for 5-7 hours, then filter, and return the filter residue to the filtrate to be added with elemental nickel, manganese or cobalt powder. Wherein step 4a) or 4c) or 4d) or 4e) can be performed once or twice. For example, these steps can be performed in the order of 4a), 4c), 4d), 4e); or 4c), 4d), 4a), 4e).

[0104] In one embodiment, step 4) comprises:

[0105] Step 4a) adjusting the pH of the filtrate to 2.9-5, preferably 2.9-3.5, with lithium-containing powder, and filtering to obtain an intermediate filtrate; passing oxygen or air or adding hydrogen peroxide to the intermediate filtrate at 50 to 70 degrees Celsius to adjust the redox potential to 280mv-500mv (measured by a potentiometer) to obtain a solid-liquid mixture; filtering the solid-liquid mixture, and then returning the filter residue to the filtrate to be adjusted to a pH of 2.9-5;

[0106] Step 4b) adjusting the pH of the filtrate to 1.5-3.0 with an acid (e.g., adding 500 ml of 30% nitric acid per cubic meter of filtrate), adding a copper nitrate solution in an amount of 1:1 to 5:1, preferably 1.2:1 to 2:1, to the molar ratio of copper nitrate to chloride ions in the filtrate, and then adding elemental copper in an amount of 1:1 to 5:1, preferably 1.2:1 to 2:1, to the molar ratio of copper to chloride ions in the filtrate, reacting at 50 to 70 degrees Celsius for 1-3 hours, and then filtering to obtain a filtrate. The nitric acid and copper nitrate added in this step 4b) can also be replaced by sulfuric acid and copper sulfate;

[0107] Step 4c) adjusting the pH of the filtrate to 3.5-5.5, preferably 3.5-4.5, with lithium-containing powder (for example, adding 1 kg of lithium-containing powder per cubic meter of filtrate), filtering, and then adding MnF2 to the filtrate at a ratio of MnF2 to the total molar number of calcium and magnesium ions in the filtrate of 1:1 to 4:1, reacting at 50 to 70 degrees Celsius for 3-5 hours, then filtering, and returning the filter residue to the filtrate to be adjusted to a pH of 3.5-5.5;

[0108] Step 4d) adding aluminum nitrate solution to the filtrate at a molar ratio of aluminum nitrate to fluoride ions in the filtrate of 1:2 to 5:1, preferably 1:2 to 1.5:1, and adding aluminum oxide powder at a molar ratio of aluminum oxide to fluoride ions in the filtrate of 1:2 to 1:1, reacting at 50 to 70 degrees Celsius for 3-5 hours, then filtering, and returning the filter residue to the filtrate to be added with aluminum nitrate solution and aluminum oxide powder. The aluminum nitrate in this step 4d) can also be replaced with aluminum sulfate; and

[0109] Step 4e) Add elemental nickel, manganese or cobalt powder to the filtrate in an amount of 5:1 to 10:1 of elemental nickel, manganese or cobalt powder to the total molar number of copper ions and aluminum ions in the filtrate, react at 50 to 70 degrees Celsius for 5-7 hours, then filter, and return the filter residue to the filtrate to be added with elemental nickel, manganese or cobalt powder. Wherein step 4a) or 4b) or 4c) or 4d) or 4e) can be performed once or twice. For example, these steps can be performed in the order of 4a), 4b), 4c), 4d), 4e); or 4b), 4c), 4d), 4a), 4e); or 4a), 4b), 4c), 4e), 4d), 4e), in which case, step 4e) is performed twice.

[0110] Due to the specific sequence of the impurity removal steps in the present application, the impurity removal steps are closely linked to each other. This connection not only removes various impurities from the final impurity removal liquid, but also does not introduce additional impurity ions; and can reduce the number of processes and production costs as a whole.

[0111] Step 5) spray pyrolysis the impurity removal liquid to obtain a lithium-containing precursor of the positive electrode material

[0112] The content of lithium, manganese, cobalt and nickel ions in the impurity removal solution obtained in step 4) can be measured by ICP, and then lithium, manganese, cobalt and nickel ions can be added to the impurity removal solution as needed according to the element ratio in the target positive electrode material, for example, one or more solutions of lithium nitrate, manganese nitrate, cobalt nitrate and nickel nitrate are added, or one or more solutions of lithium sulfate, manganese sulfate, cobalt sulfate and nickel sulfate are added.

[0113] In one embodiment, step 5) includes adding one or more solutions of lithium nitrate, manganese nitrate, cobalt nitrate, nickel nitrate or adding one or more solutions of lithium sulfate, manganese sulfate, cobalt sulfate, nickel sulfate to the impurity removal liquid, and then spraying pyrolysis the impurity removal liquid to obtain a lithium-containing precursor of the positive electrode material. Preferably, step 5) also includes adding a doping solution such as a nitrate or sulfate solution to the impurity removal liquid. The dopable solution includes, for example, a nitrate or sulfate solution of zirconium, strontium, etc.

[0114] In one embodiment, the impurity removal liquid is concentrated to control the total concentration of lithium salt, nickel salt, cobalt salt and manganese salt in the obtained solution to be 50-300 g / L. Such a metal salt concentration is conducive to atomization crystallization granulation. If the total concentration of metal salts in the solution is lower than 50 g / L, the metal salt content in the droplets after atomization will be too low, which is not conducive to the full reaction and crystallization granulation of the metal salts in the droplets during the roasting process, and the obtained product is less, which is not conducive to the enrichment of the precursor; if the total concentration of metal salts in the solution is higher than 300 g / L, the metal salt content in the droplets after atomization is too high, which is not conducive to the crystallization and granulation of the metal salt components during the roasting process, and the particle size is too large, which is not conducive to the preparation of single crystal materials, nor is it conducive to the regulation of the material crystal form, thereby reducing the stability of the positive electrode precursor. In some specific embodiments, the total concentration of lithium salt, nickel salt, cobalt salt and manganese salt in the concentrated solution of the impurity removal liquid is 50g / L, 60g / L, 80g / L, 120g / L, 160g / L, 200g / L, 220g / L, 260g / L, 300g / L, etc.

[0115] In one embodiment, the step of atomizing and calcining the solution comprises: spray pyrolysis in a spray dryer, wherein the air-to-coal ratio (air and natural gas flow ratio) of the burner is 8.5:1 to 20:1, such as 9:1 and 10:1; the pyrolysis temperature is 300-1000°C. Preferably, the air-to-coal ratio (air and natural gas flow ratio) of the burner is 8.5-10:1; atomization parameters: compressed air pressure ≥ 0.2MPA, such as 0.2-0.5MPA; compressed air and liquid flow volume ratio is 10-300:1, and the pyrolysis temperature is controlled to be 500-1000°C, such as 500, 550, 600, 650, 700, 750, 800, 850, 900, 950, 1000°C. In some embodiments, the pyrolysis temperature is controlled to be 500-680°C. The lower the pyrolysis temperature, the higher the lithium carbonate content in the precursor. The higher the pyrolysis temperature, the higher the energy consumption. The metal salt solution is atomized in a spray dryer to form droplets. The droplets quickly lose water under the action of hot air, and the metal salt undergoes pyrolysis and is converted into oxides. The nanoparticles in the droplets agglomerate to form large agglomerates, which are the precursor powders. During the spray pyrolysis process, the nano-scale primary particles aggregate into micron-scale agglomerates, which is beneficial to increase the compaction density of the nickel cobalt manganese oxide positive electrode material produced after calcination, thereby increasing the volume energy density of the nickel cobalt manganese oxide positive electrode material as a lithium ion battery electrode material. By adjusting the burner air-to-coal ratio, compressed air pressure, and compressed air and liquid flow volume ratio during the atomization roasting process, the particle size, crystal form and other physical properties of the prepared positive electrode precursor material can be flexibly controlled, which is beneficial to optimize the physicochemical properties of the positive electrode material.

[0116] In some embodiments, the calcination time is controlled to be 1 to 50 seconds. In this process, a shaped lithium-containing precursor can be prepared in a short time, the preparation time is short, the efficiency is high, and it is conducive to wide application.

[0117] In some embodiments, after the lithium-containing precursor material is prepared, post-processing steps such as grinding or crushing the lithium-containing precursor material are also included. By controlling conditions such as the grinding disc spacing or the crushing gas pressure flow rate, the particle size of the obtained product can be controlled, making the particle size distribution of the positive electrode precursor material more uniform.

[0118] This application uses waste battery positive electrode materials as the main raw materials to prepare lithium-containing precursors and positive electrode materials, which can realize resource recycling and reduce production costs; at the same time, the process of this application not only recovers precious metals such as nickel, cobalt, and manganese, but also effectively recovers lithium, and the lithium, nickel, cobalt, and manganese metal salt solutions obtained by recycling can be conveniently and efficiently used to synthesize positive electrode material precursors, reducing the process of separating metals such as lithium, nickel, cobalt, and manganese, further reducing costs. Since lithium, nickel, cobalt, and manganese metal salts have relatively high impurities, the impurity content in the impurity removal liquid of the product before spray pyrolysis is at a low level through the impurity removal treatment of this application, ensuring the low impurity content in the lithium-containing precursor product. Since this application forms a lithium-containing precursor by spray pyrolysis, compared with the coprecipitation method, the process of this application does not produce wastewater.

[0119] A second aspect of the present disclosure provides a lithium-containing precursor of a positive electrode material, which is prepared by the method of the first aspect of the present disclosure.

[0120] The lithium-containing precursor disclosed in the present application is an oxide lithium-containing precursor. When the lithium-containing precursor is sintered into a positive electrode material, no waste water is generated due to the absence of hydroxide. The lithium-containing precursor exists in the form of an oxide. Compared with a traditional hydroxide precursor, the oxide precursor has a higher content of main metals of nickel, cobalt and manganese. At the same time, the precursor also contains lithium. When sintered into a positive electrode material, the loss rate of lithium during sintering of the positive electrode material is reduced, and the yield of the finished product under the same loading amount is increased, thereby increasing the output when sintering into the positive electrode material, reducing the manufacturing cost of the positive electrode material, and greatly increasing the production line capacity.

[0121] The lithium-containing precursor in this application is formed by atomization roasting. Compared with the hydroxide precursor prepared by the coprecipitation method, the process of this application is simple, with few intermediate processes, and the reaction process is easy to flexibly control. The roasting process is carried out while atomizing, which not only ensures that the product has a smaller particle size, but also the product has a fast reaction speed. The actual reaction time of obtaining the lithium-containing precursor material by atomization roasting is only a few seconds, and the production efficiency is high. In addition, since the anions in the salt solution are converted into gaseous substances in a high temperature environment to be removed or recycled, the raw material utilization rate is high, the impurity content in the product is low, and the performance is excellent. At the same time, the lithium-containing precursor material product prepared by this method has a more excellent structural stability of the material itself relative to the traditional coprecipitation method.

[0122] The lithium-containing precursor of the present application may not contain lithium carbonate, and is represented by the chemical formula: Li a (Ni x Co y Mn 1-x-y ) (1+a), wherein a, x, and y are expressed in mol, 0.10≤a≤1.1, 0<x<1, 0<y<1, and x+y<1, and in a powder X-ray diffraction pattern using Cu-Kα rays, diffraction peaks are present at 18.7±0.3, 36.5±0.3, 37.9±0.3, 44.1±0.3, 48.4±0.3, 58.3±0.3, 64.2±0.3, and 67.9±0.3 degrees 2θ; the lithium-containing precursor includes at least one lamellar agglomerate formed by agglomeration of primary particles, and SEM observation shows that the lithium-containing precursor after the sphere is crushed is irregularly flaky. Figure 3 This is an exemplary SEM photograph of a lithium-containing precursor prepared according to the method of the present application. It can be seen that the lithium-containing precursor is in an irregular flake shape.

[0123] The lithium-containing precursor of the present application may also contain lithium carbonate, which is represented by the chemical formula: Li a (Ni x Co y Mn 1-x-y ) (1+a) (Li2CO3) z , wherein a is 0.10 to 1.08; 0<x<1, 0<y<1, and x+y<1; z is greater than 0 and less than or equal to 0.354, and its carbon content is greater than 0 and less than or equal to 6.2% by weight. In the powder x-ray diffraction pattern using Cu-Kα rays, there are diffraction peaks at 18.6±0.3, 21.2±0.3, 30.5±0.3, 31.7±0.3, 36.4±0.3, 38.0±0.3, 44.1±0.3, 48.4±0.3, 58.3±0.3, 64.2±0.3, and 67.7±0.3 degrees 2θ; the lithium-containing precursor includes at least one flaky agglomerate formed by agglomeration of primary particles. Through SEM observation, the lithium-containing precursor after the sphere is crushed is irregular flaky.

[0124] The third aspect of the present disclosure provides a positive electrode material, which is obtained by sintering the lithium-containing precursor of the positive electrode material, or by mixing the lithium-containing precursor and a supplemented lithium source (a small amount of lithium source is supplemented based on the lithium content in the lithium-containing precursor relative to the lithium content lacking in the positive electrode material) and then sintering. The lithium source can be selected from one or more of lithium carbonate, lithium hydroxide monohydrate, lithium acetate, lithium nitrate, lithium oxalate, lithium acetate, lithium hydroxide, and lithium oxide. For example, the lithium source is selected from lithium carbonate or lithium hydroxide monohydrate.

[0125] In some preferred embodiments, the positive electrode material is obtained by directly sintering the positive electrode precursor material without mixing the positive electrode precursor material with a lithium source.

[0126] Sintering can be carried out in a pure oxygen or air atmosphere, the number of sintering is 1-3 times, and the temperature of the sintering treatment is 400-1050°C. For example, the positive electrode material containing lithium precursor is kept at a first temperature of 400°C-800°C for 1-5 hours, then heated to a second temperature of 800°C-1050°C, and kept at the second temperature for 5-10 hours. Then it is naturally cooled to room temperature. The sintered product is sieved with 300 mesh to obtain the positive electrode material.

[0127] For example, the sintering is a single sintering, including heating the cathode precursor material to 750°C-1000°C at a heating rate of 5-10°C / min, and keeping the temperature at this temperature for 9h-18h. Then, the cathode precursor material is naturally cooled to room temperature. The sintered product is sieved with 300 mesh to obtain the cathode material.

[0128] For example, the positive electrode material that can be provided in the third aspect of the present disclosure is selected from NCM333, NCM523, NCM613, NCM622 and NCM811. Preferably, the positive electrode material is a high-nickel positive electrode material, including but not limited to: LiNi 0.72 Co 0.03 Mn 0.25 O2、LiNi 0.7 Co 0.04 Mn 0.26 O2、LiNi 0.67 Co 0.05 Mn 0.28 O2、LiNi 0.65 Co 0.06 Mn 0.29 O2、LiNi 0.62 Co 0.08 Mn 0.30 O2、LiNi 0.6 Co 0.10 Mn 0.30 O2, etc. These positive electrode materials also have the characteristics of good structural stability, high capacity, and good cycle stability.

[0129] The positive electrode material that can be provided in the third aspect of the present disclosure also includes lithium nickel cobalt aluminum (NCA) positive electrode material, lithium cobalt oxide positive electrode material, lithium manganese oxide positive electrode material or lithium nickel oxide positive electrode material.

[0130] A fourth aspect of the present application provides a lithium secondary battery, wherein the positive electrode sheet of the lithium secondary battery includes the positive electrode material described above.

[0131] The lithium secondary battery provided in the fourth aspect of the present application includes the above-mentioned positive electrode material in the positive electrode sheet. The positive electrode material has high gram capacity, cycle stability, structural stability and other characteristics, thereby improving the energy density, cycle stability and safety performance of the secondary battery.

[0132] In some embodiments, the positive electrode sheet in the lithium secondary battery includes a current collector and an active material layer that are laminated and bonded together, and the active material layer includes a positive electrode material, a conductive agent, a binder, and the like.

[0133] In some embodiments, the preparation process of making a positive electrode sheet from a positive electrode material is as follows: the positive electrode material, a conductive agent and a binder are mixed to obtain an electrode slurry, the electrode slurry is coated on a current collector, and a positive electrode sheet is prepared through steps such as drying, rolling, and die cutting.

[0134] In some embodiments, the positive electrode current collector includes, but is not limited to, any one of copper foil and aluminum foil.

[0135] In some embodiments, the content of the binder in the electrode slurry is 2wt%-4wt%. The binder may include one or more of polyvinylidene chloride, soluble polytetrafluoroethylene, styrene-butadiene rubber, hydroxypropyl methylcellulose, methylcellulose, carboxymethyl cellulose, polyvinyl alcohol, acrylonitrile copolymer, sodium alginate, chitosan and chitosan derivatives. In some embodiments, the content of the conductive agent in the electrode slurry is 3wt%-5wt%. The conductive agent may include one or more of graphite, carbon black, acetylene black, graphene, carbon fiber, C60 and carbon nanotubes.

[0136] The present disclosure does not specifically limit the negative electrode sheet, electrolyte, separator, etc. in the lithium secondary battery, and can be applied to conventional lithium-ion battery systems.

[0137] The present disclosure may also include the following technical solutions:

[0138] 1. A method for preparing a lithium-containing positive electrode material, comprising:

[0139] Step 1) reducing the waste lithium battery positive electrode material to obtain lithium-containing powder;

[0140] Step 2) treating the lithium-containing powder with nitric acid to obtain a corresponding metal salt solid-liquid mixture;

[0141] Step 3) filtering the metal salt solid-liquid mixture to obtain a filtrate;

[0142] Step 4) removing impurities from the filtrate to obtain a cleansed liquid;

[0143] Step 5) adding a nitrate solution to the impurity removal liquid to obtain a spray pyrolysis liquid;

[0144] Step 6) spraying and pyrolyzing the liquid to be sprayed and pyrolyzed to obtain a lithium-containing positive electrode precursor; and

[0145] Step 7) calcining the lithium-containing positive electrode precursor to obtain a lithium-containing positive electrode material.

[0146] This technical solution is Figure 2 shown.

[0147] 2. The method of scheme 1, wherein the step 1) comprises:

[0148] Step 1a) placing the waste lithium battery positive electrode material in a reduction furnace;

[0149] Step 1b) introducing a reducing agent into the reduction furnace;

[0150] Step 1c) heating the reduction furnace, and reducing the high-valent metal ions in the waste lithium battery positive electrode material to low-valent metal ions to obtain the lithium-containing powder.

[0151] 3. The method of scheme 2, wherein:

[0152] The waste lithium battery positive electrode material in step 1a) is a nickel cobalt manganese oxide (NCM) waste lithium battery positive electrode material, a nickel cobalt aluminum oxide (NCA) waste lithium battery positive electrode material, a lithium cobalt oxide waste lithium battery positive electrode material, a lithium manganese oxide waste lithium battery positive electrode material or a lithium nickel oxide waste lithium battery positive electrode material;

[0153] The reducing agent in step 1b) is selected from one or more of hydrogen, methane, carbon powder, acetylene, coal gas and liquefied petroleum gas;

[0154] The reduction furnace in step 1c) is heated to between 400 and 780 degrees Celsius, and the duration of the reduction treatment is 1 to 10 hours.

[0155] 4. The method of scheme 3, wherein

[0156] The waste lithium battery positive electrode material in step 1a) is nickel cobalt manganese oxide (NCM) or nickel cobalt aluminum oxide (NCA) waste lithium battery positive electrode material;

[0157] The reducing agent in step 1b) is methane;

[0158] The reduction furnace in step 1c) is heated to between 650 and 730 degrees Celsius, and the duration of the reduction treatment is 1 to 5 hours.

[0159] 5. The method of claim 3, wherein

[0160] The waste lithium battery positive electrode material in step 1a) is a waste lithium cobalt oxide positive electrode material, a waste lithium manganese oxide positive electrode material or a waste lithium nickel oxide positive electrode material;

[0161] The reducing agent in step 1b) is methane;

[0162] The reduction furnace in step 1c) is heated to between 600 and 680 degrees Celsius, and the duration of the reduction treatment is 1 to 5 hours.

[0163] 6. The method of any one of schemes 1 to 5, wherein step 2) comprises:

[0164] The lithium-containing powder and nitric acid are placed in a dissolving tank, the reaction temperature is 60-80 degrees Celsius, the reaction time is 1-5 hours, and the reaction obtains a solid-liquid mixture of metal salts;

[0165] The nitrogen oxides produced in the dissolution tank are absorbed by water and oxidized by oxygen to obtain nitric acid.

[0166] 7. The method of any one of schemes 1 to 6, wherein step 4) comprises:

[0167] Step 4a) adjusting the pH of the filtrate to 2.9-5 with lithium-containing powder, filtering to obtain an intermediate filtrate; passing oxygen or air or adding hydrogen peroxide to the intermediate filtrate at 50 to 70 degrees Celsius to adjust the redox potential to 280mv-500mv to obtain a solid-liquid mixture; filtering the solid-liquid mixture, and then returning the filter residue to the filtrate to be adjusted to a pH of 2.9-5.

[0168] 8. The method of any one of schemes 1 to 6, wherein step 4) comprises:

[0169] Step 4b) adjusting the pH of the filtrate to 1.5-3.0 with nitric acid, adding copper nitrate solution in an amount of 1:1 to 5:1 of copper nitrate to chloride ions in the filtrate, adding elemental copper in an amount of 1:1 to 5:1 of copper to chloride ions in the filtrate, and reacting at 50 to 70 degrees Celsius for 1 to 3 hours.

[0170] 9. The method of any one of schemes 1-6, wherein step 4) comprises:

[0171] Step 4c) The pH of the filtrate is adjusted to 3.5-5.5 with lithium-containing powder, filtered, and then MnF2 is added to the filtrate at a ratio of MnF2 to the total molar number of calcium and magnesium ions in the filtrate of 1:1 to 4:1, reacted at 50 to 70 degrees Celsius for 3-5 hours, then filtered, and the filter residue is returned to the filtrate to be adjusted to a pH of 3.5-5.5.

[0172] 10. The method of any one of schemes 1-6, wherein step 4) comprises:

[0173] Step 4d) adding aluminum nitrate solution to the filtrate in a molar ratio of aluminum nitrate to fluoride ions in the filtrate of 1:2 to 1.5:1, adding aluminum oxide powder in a molar ratio of aluminum oxide to fluoride ions in the filtrate of 1:2 to 1:1, reacting at 50 to 70 degrees Celsius for 3-5 hours, then filtering, and returning the filter residue to the filtrate to be added with aluminum nitrate solution and aluminum oxide powder.

[0174] 11. The method of any one of schemes 1 to 6, wherein step 4) comprises:

[0175] Step 4e) adding elemental nickel, manganese or cobalt powder to the filtrate in a ratio of 5:1 to 10:1 of elemental nickel, manganese or cobalt powder to the total molar number of copper ions and aluminum ions in the filtrate, reacting at 50 to 70 degrees Celsius for 5-7 hours, then filtering, and returning the filter residue to the filtrate to be added with elemental nickel, manganese or cobalt powder.

[0176] 12. The method of any one of schemes 1 to 6, wherein step 4) comprises:

[0177] Step 4a) adjusting the pH of the filtrate to 2.9-5 with lithium-containing powder, filtering to obtain an intermediate filtrate A; passing oxygen or air or adding hydrogen peroxide to the intermediate filtrate A at 50 to 70 degrees Celsius to adjust the redox potential to 280mv-500mv to obtain a solid-liquid mixture; filtering the solid-liquid mixture, and then returning the filter residue to the filtrate to be adjusted to a pH of 2.9-5;

[0178] Step 4c) adjusting the pH of the filtrate to 3.5-5.5 with lithium-containing powder, filtering, and then adding MnF2 to the filtrate at a ratio of MnF2 to the total molar number of calcium and magnesium ions in the filtrate of 1:1 to 4:1, reacting at 50 to 70 degrees Celsius for 3-5 hours, then filtering, and returning the filter residue to the filtrate to be adjusted to a pH of 3.5-5.5;

[0179] Step 4d) adding aluminum nitrate solution to the filtrate in a molar ratio of aluminum nitrate to fluoride ions in the filtrate of 1:2 to 1.5:1, adding aluminum oxide powder in a molar ratio of aluminum oxide to fluoride ions in the filtrate of 1:2 to 1:1, reacting at 50 to 70 degrees Celsius for 3-5 hours, then filtering, and returning the filter residue to the filtrate to be added with aluminum nitrate solution and aluminum oxide powder; and

[0180] Step 4e) adding elemental nickel, manganese or cobalt powder to the filtrate in a ratio of 5:1 to 10:1 of elemental nickel, manganese or cobalt powder to the total molar number of copper ions and aluminum ions in the filtrate, reacting at 50 to 70 degrees Celsius for 5-7 hours, then filtering, and returning the filter residue to the filtrate to be added with elemental nickel, manganese or cobalt powder.

[0181] 13. The method of scheme 12, wherein steps 4a), 4c), 4d), and 4e) are performed in the following order:

[0182] 4a), 4c), 4d), 4e); or

[0183] 4c), 4d), 4a), 4e).

[0184] 14. The method of scheme 12, wherein step 4) further comprises:

[0185] Step 4b) adjusting the pH of the filtrate to 1.5-3.0 with nitric acid, adding copper nitrate solution in an amount of 1:1 to 5:1 of copper nitrate to chloride ions in the filtrate, adding copper in an amount of 1:1 to 5:1 of copper to chloride ions in the filtrate, and reacting at 50 to 70 degrees Celsius for 1 to 3 hours.

[0186] 15. The method of scheme 14, wherein steps 4a), 4b), 4c), 4d), and 4e) are performed in the following order:

[0187] 4a), 4b), 4c), 4d), 4e); or

[0188] 4a), 4b), 4c), 4e), 4d), 4e).

[0189] 16. The method of any one of Schemes 1 to 15, wherein the nitrate solution in step 5) comprises one or more solutions of lithium nitrate, manganese nitrate, cobalt nitrate, and nickel nitrate.

[0190] 17. The method of any one of Schemes 1-16, wherein step 5) further comprises adding a doping solution to the impurity removal solution.

[0191] 18. The method of Scheme 17, wherein the doping solution in step 5) comprises one or more solutions of zirconium nitrate, strontium nitrate, and aluminum nitrate.

[0192] 19. The method of any one of schemes 1-18, wherein

[0193] The spray pyrolysis in step 6) is carried out in a spray pyrolysis device, wherein the burner air-to-coal ratio (ratio of air and natural gas flow) is 8.5-20:1; and the pyrolysis temperature is 300-1000°C.

[0194] 20. The method of scheme 19, wherein the spray pyrolysis in step 6) adopts a burner air-to-coal ratio (air and natural gas flow ratio) of 8.5-10:1; the atomization parameters adopt a compressed air pressure ≥ 0.2MPA, a compressed air and liquid flow volume ratio of 10-300:1, and a pyrolysis temperature of 500-1000°C.

[0195] 21. The method of any one of Schemes 1-20, step 6) further comprises crushing the lithium-containing positive electrode precursor after spray pyrolysis.

[0196] 22. The method of any one of schemes 1-21, wherein step 7) comprises keeping the lithium-containing positive electrode precursor at a first temperature of 400°C-800°C for 1-5 hours, and keeping it at a second temperature of 800°C-1050°C for 5-10 hours.

[0197] 23. The method of any one of schemes 1-21, wherein step 7) comprises sintering a lithium-containing positive electrode precursor, during sintering, directly raising the temperature to a maximum sintering temperature, and maintaining the temperature at the maximum sintering temperature for 5-15 hours to obtain a positive electrode material, wherein the maximum sintering temperature is 300°C-1000°C.

[0198] 24. A positive electrode material prepared by the method of any one of schemes 1 to 23.

[0199] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the embodiments of the present invention are clearly and completely described below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be understood as limiting the present invention. Based on the described embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should belong to the scope of protection of the present invention.

[0200] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, etc. used in the following examples are all commercially available unless otherwise specified.

[0201] Example 1

[0202] Experiment 1.1: Preparation of lithium-containing precursors for cathode materials

[0203] The positive electrode material of the waste lithium battery of nickel cobalt manganese oxide is placed in a reduction furnace; natural gas is introduced into the reduction furnace; the reduction furnace is heated to 680 degrees Celsius and kept warm for 3 hours to obtain lithium-containing powder.

[0204] Then, the lithium-containing powder is placed in a dissolving tank, 8 liters of 30% nitric acid is added per kilogram of lithium-containing powder at a rate of 100 mL per minute, and the mixture is reacted at 70 degrees Celsius for 2 hours to obtain a solid-liquid mixture of metal salts.

[0205] Then, the metal salt solid-liquid mixture is filtered to obtain a filtrate. The filtrate is subjected to the following impurity removal steps:

[0206] a) adjusting the pH of the filtrate to about 3.5 with lithium-containing powder, filtering to obtain a filtrate; passing air through the filtrate at 60 degrees Celsius to adjust the redox potential to about 350 mv to obtain a solid-liquid mixture; filtering the solid-liquid mixture to remove precipitates to obtain a filtrate;

[0207] b) adjusting the pH of the filtrate in the previous step to 2.5 by adding 500 ml of 30% nitric acid per cubic meter of filtrate, testing the chloride ion concentration in the filtrate with a potentiometric titrator (silver nitrate standard titration solution), adding copper nitrate solution in an amount of 1.5:1 molar ratio of copper nitrate to chloride ions in the filtrate, and then adding elemental copper in an amount of 1.5:1 molar ratio of copper to chloride ions in the filtrate, and reacting at 60 degrees Celsius for 2 hours;

[0208] c) adjusting the pH of the filtrate in the previous step to about 4 with lithium-containing powder, filtering, and then measuring the total concentration of calcium and magnesium ions in the filtrate by ICP, adding MnF2 to the filtrate at a ratio of about 2:1 to the total molar number of calcium and magnesium ions in the filtrate, reacting at about 60 degrees Celsius for 4 hours, and then filtering to obtain a filtrate;

[0209] d) measuring the fluoride ion concentration of the filtrate in the previous step by a fluoride ion selective electrode and a saturated calomel electrode, adding aluminum nitrate solution in an amount of 1:1 molar ratio of aluminum nitrate to fluoride ions in the filtrate, adding aluminum oxide powder in an amount of 1:1 molar ratio of aluminum oxide to fluoride ions in the filtrate, reacting at 60 degrees Celsius for 4 hours, and then filtering to obtain a filtrate;

[0210] e) measuring the concentrations of copper ions and aluminum ions in the filtrate of the previous step by ICP, adding single nickel powder to the filtrate in an amount of 6:1 with a ratio of single nickel powder to the total molar number of copper ions and aluminum ions in the filtrate, reacting at 60 degrees Celsius for 6 hours, and then filtering to obtain a filtrate.

[0211] ICP measured the concentrations of Ni, Mn, Co, and Li ions in the filtrate after impurities were removed, and the nitrate solutions of nickel, cobalt, manganese, and lithium were supplemented according to the molar ratio of Ni:Mn:Co:Li=0.60:0.10:0.30:1.05, and then concentrated. The total concentration of nickel nitrate, cobalt nitrate, manganese nitrate, and lithium nitrate in the concentrate was about 186 g / L.

[0212] The concentrated liquid is passed into the synthesis tower for spray pyrolysis, and the powder is discharged from the bottom. The powder is cooled by the cooler, then sieved, air flow crushed, demagnetized, and packaged as a finished product. The flue gas is drawn from the top by a fan, and the dust in the flue gas is washed and cooled by the Venturi. After the exhaust gas temperature is reduced to less than 30 degrees Celsius by the heat exchanger, the nitric acid is recovered by multi-stage absorption, and finally the exhaust gas is discharged up to the standard after alkali washing and urea absorption.

[0213] Spray pyrolysis parameters: burner air-coal ratio (air and natural gas flow ratio): 10:1;

[0214] Atomization parameters: Compressed air pressure: 0.3MPA;

[0215] Compressed air and liquid flow volume ratio: 175:1;

[0216] The temperature of the spray pyrolysis was 750°C, and the calcination time was 10 seconds.

[0217] Experiment 1.2: Preparation of positive electrode materials

[0218] In a pure oxygen atmosphere, the positive electrode material containing lithium precursor of Experiment 1.1 was sintered at 900℃ for 10 hours and then cooled naturally. 0.6 Co 0.1 Mn 0.3 O2 positive electrode material.

[0219] Experiment 1.3: Preparation of Lithium-ion Batteries

[0220] The steps for preparing lithium-ion batteries include:

[0221] Preparation of positive electrode sheet: According to the weight ratio of positive electrode material: conductive agent (acetylene black): binder (PVDF) in Experiment 1.2 of 85%: 10%: 5%, weigh and mix and grind. Then, add N-methylpyrrolidone (NMP) solvent to prepare a uniform positive electrode slurry. Use a scraper to evenly apply the positive electrode slurry on the aluminum foil, and dry it to obtain a positive electrode sheet that can be directly assembled into the battery.

[0222] Battery assembly: In a glove box with a high-purity argon atmosphere, the prepared positive electrode sheet was assembled into a button-type battery of model CR2025 to form a button-type battery with lithium as the counter electrode for subsequent electrochemical performance testing. The separator was a polyolefin porous membrane and the electrolyte was ethylene carbonate.

[0223] The experiment measured that the first discharge capacity was 190.3mAh / g at a charge and discharge voltage of 3.0 to 4.4V, a temperature of 25°C, and a 0.1C charge and discharge capacity. The first coulombic efficiency was 90.1%, and the 50-cycle discharge capacity retention rate was 90.7%.

[0224] Example 2

[0225] Experiment 2.1: Preparation of lithium-containing precursors for cathode materials

[0226] The waste lithium manganate lithium battery positive electrode material is placed in a reduction furnace; natural gas is introduced into the reduction furnace; the reduction furnace is heated to 640 degrees Celsius and kept warm for 3 hours to obtain lithium-containing powder.

[0227] Then, the lithium-containing powder is placed in a dissolving tank, 8 liters of 30% nitric acid is added per kilogram of lithium-containing powder at a rate of 100 mL per minute, and the mixture is reacted at 70 degrees Celsius for 2 hours to obtain a solid-liquid mixture of metal salts.

[0228] Then, the metal salt solid-liquid mixture is filtered to obtain a filtrate. The filtrate is subjected to the following impurity removal steps:

[0229] a) adjusting the pH of the filtrate to about 3.5 with lithium-containing powder, filtering to obtain a filtrate; passing air through the filtrate at 60 degrees Celsius to adjust the redox potential to about 350 mv to obtain a solid-liquid mixture; filtering the solid-liquid mixture to remove precipitates to obtain a filtrate;

[0230] b) adjusting the pH of the filtrate in the previous step to 2.5 by adding 500 ml of 30% nitric acid per cubic meter of filtrate, testing the chloride ion concentration in the filtrate with a potentiometric titrator (silver nitrate standard titration solution), adding copper nitrate solution in an amount of 1.5:1 molar ratio of copper nitrate to chloride ions in the filtrate, and then adding elemental copper in an amount of 1.5:1 molar ratio of copper to chloride ions in the filtrate, and reacting at 60 degrees Celsius for 2 hours;

[0231] c) adjusting the pH of the filtrate in the previous step to about 4 with lithium-containing powder, filtering, and then measuring the total concentration of calcium and magnesium ions in the filtrate by ICP, adding MnF2 to the filtrate at a ratio of about 2:1 to the total molar number of calcium and magnesium ions in the filtrate, reacting at about 60 degrees Celsius for 4 hours, and then filtering to obtain a filtrate;

[0232] d) measuring the fluoride ion concentration of the filtrate in the previous step by a fluoride ion selective electrode and a saturated calomel electrode, adding aluminum nitrate solution in an amount of 1:1 molar ratio of aluminum nitrate to fluoride ions in the filtrate, adding aluminum oxide powder in an amount of 1:1 molar ratio of aluminum oxide to fluoride ions in the filtrate, reacting at 60 degrees Celsius for 4 hours, and then filtering to obtain a filtrate;

[0233] e) measuring the concentrations of copper ions and aluminum ions in the filtrate of the previous step by ICP, adding single nickel powder to the filtrate in an amount of 6:1 with a ratio of single nickel powder to the total molar number of copper ions and aluminum ions in the filtrate, reacting at 60 degrees Celsius for 6 hours, and then filtering to obtain a filtrate.

[0234] ICP measured the concentrations of Ni, Mn, Co, and Li ions in the filtrate after impurity removal, and supplemented the nitrate solutions of nickel, cobalt, and manganese according to the molar ratio of Ni:Mn:Co:Li=0.60:0.10:0.30:1.05, and then concentrated. The total concentration of nickel nitrate, cobalt nitrate, manganese nitrate, and lithium nitrate in the concentrate was about 180 g / L.

[0235] The concentrated liquid is passed into the synthesis tower for spray pyrolysis, and the powder is discharged from the bottom. The powder is cooled by the cooler, then sieved, air flow crushed, demagnetized, and packaged as a finished product. The flue gas is drawn from the top by a fan, and the dust in the flue gas is washed and cooled by the Venturi. After the exhaust gas temperature is reduced to less than 30 degrees Celsius by the heat exchanger, the nitric acid is recovered by multi-stage absorption, and finally the exhaust gas is discharged up to the standard after alkali washing and urea absorption.

[0236] Spray pyrolysis parameters: burner air-coal ratio (air and natural gas flow ratio): 10:1;

[0237] Atomization parameters: Compressed air pressure: 0.3MPA;

[0238] Compressed air and liquid flow volume ratio: 175:1;

[0239] The temperature of the spray pyrolysis was 750°C, and the calcination time was 10 seconds.

[0240] Experiment 2.2: Preparation of positive electrode materials

[0241] In a pure oxygen atmosphere, the positive electrode material containing lithium precursor of Experiment 2.1 was sintered at 960℃ for 10 hours and then cooled naturally. 0.6 Co 0.1 Mn 0.3 O2 positive electrode material.

[0242] Experiment 2.3: Preparation of Lithium-ion Batteries

[0243] The steps for preparing lithium-ion batteries include:

[0244] Preparation of positive electrode sheet: According to the weight ratio of positive electrode material: conductive agent (acetylene black): binder (PVDF) in Experiment 2.2 of 85%: 10%: 5%, weigh and mix and grind. Then, add N-methylpyrrolidone (NMP) solvent to prepare a uniform positive electrode slurry. Use a scraper to evenly apply the positive electrode slurry on the aluminum foil, and dry it to obtain a positive electrode sheet that can be directly assembled into the battery.

[0245] Battery assembly: In a glove box with a high-purity argon atmosphere, the prepared positive electrode sheet was assembled into a button-type battery of model CR2025 to form a button-type battery with lithium as the counter electrode for subsequent electrochemical performance testing. The separator was a polyolefin porous membrane and the electrolyte was ethylene carbonate.

[0246] The experiment measured that the first discharge capacity was 191.1mAh / g at a charge and discharge voltage of 3.0 to 4.4V, a temperature of 25°C, and a 0.1C charge and discharge capacity. The first coulombic efficiency was 90.4%, and the 50-cycle discharge capacity retention rate was 90.9%.

[0247] Example 3

[0248] Experiment 3.1: Preparation of lithium-containing precursors for cathode materials

[0249] The positive electrode material of the waste lithium battery of nickel cobalt manganese oxide is placed in a reduction furnace; natural gas is introduced into the reduction furnace; the reduction furnace is heated to 680 degrees Celsius and kept warm for 3 hours to obtain lithium-containing powder.

[0250] Then, the lithium-containing powder is placed in a dissolving tank, 15 liters of 10% sulfuric acid is added per kilogram of lithium-containing powder at a rate of 150 mL per minute, and the mixture is reacted at 70 degrees Celsius for 2 hours to obtain a solid-liquid mixture of metal salts.

[0251] Then, the metal salt solid-liquid mixture is filtered to obtain a filtrate. The filtrate is subjected to the following impurity removal steps:

[0252] a) adjusting the pH of the filtrate to about 3.5 with lithium-containing powder, filtering to obtain a filtrate; passing air through the filtrate at 60 degrees Celsius to adjust the redox potential to about 350 mv to obtain a solid-liquid mixture; filtering the solid-liquid mixture to remove precipitates to obtain a filtrate;

[0253] c) adjusting the pH of the filtrate in the previous step to about 4 with lithium-containing powder, filtering, and then measuring the total concentration of calcium and magnesium ions in the filtrate by ICP, adding MnF2 to the filtrate at a ratio of about 2:1 to the total molar number of calcium and magnesium ions in the filtrate, reacting at about 60 degrees Celsius for 4 hours, and then filtering to obtain a filtrate;

[0254] d) measuring the fluoride ion concentration of the filtrate in the previous step by a fluoride ion selective electrode and a saturated calomel electrode, adding aluminum sulfate solution in an amount such that the molar ratio of aluminum sulfate to fluoride ions in the filtrate is 1:1, adding aluminum oxide powder in an amount such that the molar ratio of aluminum oxide to fluoride ions in the filtrate is 1:1, reacting at 60 degrees Celsius for 4 hours, and then filtering to obtain a filtrate;

[0255] e) measuring the concentrations of copper ions and aluminum ions in the filtrate of the previous step by ICP, adding single nickel powder to the filtrate in an amount of 6:1 with a ratio of single nickel powder to the total molar number of copper ions and aluminum ions in the filtrate, reacting at 60 degrees Celsius for 6 hours, and then filtering to obtain a filtrate.

[0256] ICP measured the concentrations of Ni, Mn, Co, and Li ions in the filtrate after impurities were removed, and the sulfate solutions of nickel, cobalt, manganese, and lithium were added according to the molar ratio of Ni:Mn:Co:Li=0.60:0.10:0.30:1.05, and then concentrated. The total concentration of nickel sulfate, cobalt sulfate, manganese sulfate, and lithium sulfate in the concentrate was about 210 g / L.

[0257] The concentrated liquid is passed into the synthesis tower for spray pyrolysis, and the powder is discharged from the bottom. The powder is cooled by the cooler, then sieved, air flow crushed, demagnetized, and packaged as finished products. The flue gas is drawn from the top by the fan, and the dust in the flue gas is washed and cooled by the Venturi. After the exhaust gas temperature is reduced to less than 30 degrees Celsius by the heat exchanger, sulfuric acid is recovered through multi-stage absorption, and finally the exhaust gas is discharged up to the standard after alkali washing and urea absorption.

[0258] Spray pyrolysis parameters: burner air-coal ratio (air and natural gas flow ratio): 10:1;

[0259] Atomization parameters: Compressed air pressure: 0.3MPA;

[0260] Compressed air and liquid flow volume ratio: 175:1;

[0261] The temperature of the spray pyrolysis was 750°C, and the calcination time was 10 seconds.

[0262] Experiment 3.2: Preparation of positive electrode materials

[0263] In a pure oxygen atmosphere, the positive electrode material containing lithium precursor of Experiment 3.1 was sintered at 900℃ for 10 hours and then cooled naturally. 0.6 Co 0.1 Mn 0.3 O2 positive electrode material.

[0264] Experiment 3.3: Preparation of Lithium-ion Batteries

[0265] The steps for preparing lithium-ion batteries include:

[0266] Preparation of positive electrode sheet: According to the weight ratio of positive electrode material: conductive agent (acetylene black): binder (PVDF) in Experiment 3.2 of 85%: 10%: 5%, weigh and mix and grind. Then, add N-methylpyrrolidone (NMP) solvent to prepare a uniform positive electrode slurry. Use a scraper to evenly apply the positive electrode slurry on the aluminum foil, and dry it to obtain a positive electrode sheet that can be directly assembled into the battery.

[0267] Battery assembly: In a glove box with a high-purity argon atmosphere, the prepared positive electrode sheet was assembled into a button-type battery of model CR2025 to form a button-type battery with lithium as the counter electrode for subsequent electrochemical performance testing. The separator was a polyolefin porous membrane and the electrolyte was ethylene carbonate.

[0268] The experiment measured that the first discharge capacity was 188.7mAh / g at a charge and discharge voltage of 3.0 to 4.4V, a temperature of 25°C, and a 0.1C charge and discharge capacity. The first coulombic efficiency was 88.6%, and the 50-week discharge capacity retention rate was 89.2%.

[0269] The present invention illustrates the process method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

[0270] In the absence of conflict, the embodiments of the present invention and the features in the embodiments can be combined with each other to obtain new embodiments. The protection scope of the present invention is not limited to the above-mentioned embodiments, and the protection scope of the present invention shall be based on the protection scope of the claims.

Claims

1. A method for preparing a lithium-containing precursor of a positive electrode material, comprising: Step 1) reducing the waste lithium battery positive electrode material to obtain lithium-containing powder; Step 2) treating the lithium-containing powder with at least one acid selected from oxalic acid, acetic acid, formic acid, nitric acid, sulfuric acid, and hydrochloric acid to obtain a corresponding metal salt solid-liquid mixture; Step 3) filtering the metal salt solid-liquid mixture to obtain a filtrate; Step 4) removing impurities from the filtrate to obtain a cleansed liquid; and Step 5) spray pyrolysis the impurity removal liquid to obtain a lithium-containing precursor of the positive electrode material.

2. The method of claim 1, wherein said step 1) comprises: Step 1a) placing the waste lithium battery positive electrode material in a reduction furnace; Step 1b) introducing a reducing agent into the reduction furnace; and Step 1c) heating the reduction furnace, and reducing the high-valent metal ions in the waste lithium battery positive electrode material to low-valent metal ions to obtain the lithium-containing powder.

3. The method of claim 2, wherein: The waste lithium battery positive electrode material in step 1a) is a nickel cobalt manganese oxide (NCM) waste lithium battery positive electrode material, a nickel cobalt aluminum oxide (NCA) waste lithium battery positive electrode material, a lithium cobalt oxide waste lithium battery positive electrode material, a lithium manganese oxide waste lithium battery positive electrode material or a lithium nickel oxide waste lithium battery positive electrode material; The reducing agent in step 1b) is selected from one or more of hydrogen, methane, carbon powder, acetylene, coal gas and liquefied petroleum gas.

4. The method of claim 2, wherein said step 1c) comprises: The reduction furnace is heated to between 300-880 degrees Celsius, and the duration of the reduction treatment is 0.5-20 hours.

5. The method of claim 2, wherein The waste lithium battery positive electrode material in step 1a) is nickel cobalt manganese oxide (NCM) or nickel cobalt aluminum oxide (NCA) waste lithium battery positive electrode material; The reducing agent in step 1b) is methane; The reduction furnace in step 1c) is heated to between 650 and 730 degrees Celsius, and the duration of the reduction treatment is 1 to 5 hours.

6. The method of claim 2, wherein The waste lithium battery positive electrode material in step 1a) is a waste lithium cobalt oxide positive electrode material, a waste lithium manganese oxide positive electrode material or a waste lithium nickel oxide positive electrode material. The reducing agent in step 1b) is methane; The reduction furnace in step 1c) is heated to between 600 and 680 degrees Celsius, and the duration of the reduction treatment is 1 to 5 hours.

7. The method of any one of claims 1 to 6, wherein step 2) comprises: Placing the lithium-containing powder and the at least one acid into a dissolving tank to react to obtain a solid-liquid mixture of metal salts; Recycle waste from the dissolving tank.

8. The method of claim 7, wherein The at least one acid is nitric acid, sulfuric acid, hydrochloric acid or a mixture thereof; the reaction temperature of the at least one acid and the lithium-containing powder is 60-80 degrees Celsius, and the reaction time is 1-5 hours.

9. The method of claim 7, wherein The waste generated in the recovery dissolution tank includes: Nitrogen oxides or sulfur oxides produced by the reaction of acid with lithium-containing powder are not discharged from the dissolution tank, but are absorbed by water and oxidized by oxygen to obtain nitric acid / sulfuric acid in the dissolution tank.

10. The method of any one of claims 1 to 9, wherein step 4) comprises: Step 4a) adjusting the pH of the filtrate to 2.9-5 with lithium-containing powder, filtering to obtain an intermediate filtrate; passing oxygen or air or adding hydrogen peroxide to the intermediate filtrate at 50 to 70 degrees Celsius to adjust the redox potential to 280mv-500mv to obtain a solid-liquid mixture; filtering the solid-liquid mixture, and then returning the filter residue to the filtrate to be adjusted to a pH of 2.9-5.

11. The method of any one of claims 1 to 9, wherein step 4) comprises: Step 4b) adjusting the pH of the filtrate to 1.5-3.0 with nitric acid, adding copper nitrate solution in an amount of 1:1 to 5:1 of copper nitrate to chloride ions in the filtrate, adding elemental copper in an amount of 1:1 to 5:1 of copper to chloride ions in the filtrate, reacting at 50 to 70 degrees Celsius for 1 to 3 hours to obtain a solid-liquid mixture; filtering the solid-liquid mixture to obtain a filtrate.

12. The method of any one of claims 1 to 9, wherein step 4) comprises: Step 4c) The pH of the filtrate is adjusted to 3.5-5.5 with lithium-containing powder, filtered, and then MnF2 is added to the filtrate at a ratio of MnF2 to the total molar number of calcium and magnesium ions in the filtrate of 1:1 to 4:1, reacted at 50 to 70 degrees Celsius for 3-5 hours, then filtered, and the filter residue is returned to the filtrate to be adjusted to a pH of 3.5-5.

5.

13. The method of any one of claims 1 to 9, wherein step 4) comprises: Step 4d) adding aluminum nitrate solution to the filtrate in a molar ratio of aluminum nitrate to fluoride ions in the filtrate of 1:2 to 1.5:1, adding aluminum oxide powder in a molar ratio of aluminum oxide to fluoride ions in the filtrate of 1:2 to 1:1, reacting at 50 to 70 degrees Celsius for 3-5 hours, then filtering, and returning the filter residue to the filtrate to be added with aluminum nitrate solution and aluminum oxide powder.

14. The method of any one of claims 1 to 9, wherein step 4) comprises: Step 4e) adding elemental nickel, manganese or cobalt powder to the filtrate in a ratio of 5:1 to 10:1 of elemental nickel, manganese or cobalt powder to the total molar number of copper ions and aluminum ions in the filtrate, reacting at 50 to 70 degrees Celsius for 5-7 hours, then filtering, and returning the filter residue to the filtrate to be added with elemental nickel, manganese or cobalt powder.

15. The method of any one of claims 1 to 9, wherein step 4) comprises: Step 4a) adjusting the pH of the filtrate to 2.9-5 with lithium-containing powder, and filtering to obtain an intermediate filtrate A; Passing oxygen or air or adding hydrogen peroxide to the intermediate filtrate A at 50 to 70 degrees Celsius to adjust the redox potential to 280mv-500mv to obtain a solid-liquid mixture; filtering the solid-liquid mixture, and then returning the filter residue to the filtrate to be adjusted to a pH of 2.9-5; Step 4c) adjusting the pH of the filtrate to 3.5-5.5 with lithium-containing powder, filtering, and then adding MnF2 to the filtrate at a ratio of MnF2 to the total molar number of calcium and magnesium ions in the filtrate of 1:1 to 4:1, reacting at 50 to 70 degrees Celsius for 3-5 hours, then filtering, and returning the filter residue to the filtrate to be adjusted to a pH of 3.5-5.5; Step 4d) adding aluminum nitrate solution to the filtrate in a molar ratio of aluminum nitrate to fluoride ions in the filtrate of 1:2 to 1.5:1, adding aluminum oxide powder in a molar ratio of aluminum oxide to fluoride ions in the filtrate of 1:2 to 1:1, reacting at 50 to 70 degrees Celsius for 3-5 hours, then filtering, and returning the filter residue to the filtrate to be added with aluminum nitrate solution and aluminum oxide powder; and Step 4e) adding elemental nickel, manganese or cobalt powder to the filtrate in a ratio of 5:1 to 10:1 of elemental nickel, manganese or cobalt powder to the total molar number of copper ions and aluminum ions in the filtrate, reacting at 50 to 70 degrees Celsius for 5-7 hours, then filtering, and returning the filter residue to the filtrate to be added with elemental nickel, manganese or cobalt powder.

16. The method of claim 15, wherein steps 4a), 4c), 4d), and 4e) are performed in the following order: 4a), 4c), 4d), 4e); or 4c), 4d), 4a), 4e).

17. The method of claim 15, wherein step 4) further comprises: Step 4b) adjusting the pH of the filtrate to 1.5-3.0 with nitric acid, adding copper nitrate solution in an amount of 1:1 to 5:1 of copper nitrate to chloride ions in the filtrate, adding copper in an amount of 1:1 to 5:1 of copper to chloride ions in the filtrate, and reacting at 50 to 70 degrees Celsius for 1 to 3 hours.

18. The method of claim 17, wherein steps 4a), 4b), 4c), 4d), and 4e) are performed in the following order: 4a), 4b), 4c), 4d), 4e); or 4a), 4b), 4c), 4e), 4d), 4e).

19. The method according to any one of claims 1 to 18, wherein step 5) comprises adding one or more solutions of lithium nitrate, manganese nitrate, cobalt nitrate, and nickel nitrate to the impurity removal solution, and then spray pyrolyzing the impurity removal solution to obtain a lithium-containing precursor of the positive electrode material.

20. The method of any one of claims 1 to 19, wherein The spray pyrolysis in step 5) is carried out in a spray dryer, wherein the burner air-to-coal ratio (ratio of air and natural gas flow) is 8.5-20:1; and the pyrolysis temperature is 300-1000°C.

21. The method of claim 20, wherein the spray pyrolysis in step 5) adopts a burner air-to-coal ratio (air and natural gas flow ratio) of 8.5-10:1; the atomization parameters adopt a compressed air pressure ≥ 0.2 MPA, a compressed air and liquid flow volume ratio of 10-300:1, and a pyrolysis temperature of 500-1000°C.

22. The method according to any one of claims 1 to 21, wherein step 5) further comprises crushing the lithium-containing precursor of the positive electrode material after the spray pyrolysis.

23. A lithium-containing precursor of a positive electrode material, prepared by the method according to any one of claims 1 to 22.

24. A method for preparing a positive electrode material, comprising calcining the lithium-containing precursor of the positive electrode material according to claim 23 to obtain a lithium-containing positive electrode material.

25. The method of claim 24, wherein the calcining comprises keeping the positive electrode material lithium-containing precursor at a first temperature of 400°C-800°C for 1-5 hours, and keeping it at a second temperature of 800°C-1050°C for 5-10 hours.

26. The method of claim 24, wherein the calcination comprises sintering a lithium-containing precursor of the positive electrode material, during sintering, directly raising the temperature to a maximum sintering temperature, and maintaining the temperature at the maximum sintering temperature for 5-15 hours to obtain the positive electrode material, wherein the maximum sintering temperature is 300°C-1000°C.

27. A positive electrode material prepared by the method of any one of Schemes 24-26.